Efecto de bioinsumos de residuo de pescado y Bacillus spp. en el cultivo maní (Arachis hypogaea L.) variedad INIAP 382 - Pacheco Erazo, Diego Ismael (2025)
This research was conducted with the objective of evaluating the effect of fish residue-based bioproducts and Bacillus spp. on peanut (Arachis hypogaea L.) cultivation, variety INIAP 382. Nine microorganism-based treatments with different application frequencies were used: Fish bioproducts / high (T1), Fish bioproducts / medium (T2), Fish bioproducts / low (T3), Bacillus / high (T4), Bacillus / medium (T5), Bacillus / low (T6), Fish bioproducts + Bacillus / high (T7), Fish bioproducts + Bacillus / medium (T8), Fish bioproducts + Bacillus / low (T9), and the control. A factorial completely randomized block design (CRBD) (AxB+1) with 3 replications was used. No statistically significant differences were observed in any of the treatments when fish bioproducts were combined with Bacillus for the variables number of grains, weight of 100 grains, and yield, while the pod set percentage was statistically influenced. Therefore, the use of both microorganisms, alone or combined, allows for increased values in certain productive variables of peanut cultivation.